AB0736 Strategy for the Early Detection and Referral of Patients with Suspected Spondyloarthritis. (10th June 2014) - Juanola, X.; Collantes, E.; Leόn, F.; Torres, A.; García de Yébenes, M.J.; Queiro, R.; Gratacόs, J.; García Criado, E.; Giménez, S.; Carmona, L.
Abstract : Objectives: To design a strategy for early detection and referral of patients with suspected spondyloarthritis (SpA) by primary care physicians (PCP). Methods: We used a modified RAND/UCLA methodology and systematic review (SR). A discussion group, formed by rheumatologists and PCP, discussed the process map and proposed recommendations and algorithms. These, together with the results of the SR, underwent 2 Delphi rounds to assess acceptance by a large group of users. Results: The recommendations and grade of agreement are presnted in Table 1 ). Conclusions: Any chronic (>3 months) LBP in <45 years patients should be investigated in 4 phases 1) key questions, 2) extra questions, 3) physical examination, and 4) additional tests. They should be referred to rheumatology if having 1) IBP, 2) signs suggestive of SpA, or 3) HLA B27+, elevated CRP, or sacroiliitis. Recommendations on the referral process are included. Acknowledgements: This project was supported by a grant from MSD. Disclosure of Interest: X. Juanola: None declared, E. Collantes: None declared, F. Leόn: None declared, A. Torres: None declared, M. J. García de Yébenes: None declared, R. Queiro: None declared, J. Gratacόs: None declared, E. García Criado: None declared, S. Giménez: None declared, L. Carmona Grant/research support: Abbvie, MSD, Roche, Speakers bureau: Roche, Pfizer DOI: 10.1136/annrheumdis-2014-eular.1812